Establishing Shipyards’ BPR Key CSF’S during Revamping Project Disbursement Process - Ismail, Azman; Osman, NorHasni (International Journal of Engineering and Technology, 2018)
BPR is a great management tools used to revamp a business process within anorganization. Nowadays, most of the organization have reach its maturity stage and adaptation of BPRCSFâ€™s must be scrutinize to ensure that the intended BPR objectives are fulfilled. The Shipyard, whilerevamping its project disbursement process came across with a lot of CSFâ€™s, but only a few are thekey CSFâ€™s that help to move forward with the BPR change initiative. This research used qualitativemethod with interactive Action Research Cycle to identify and establish Shipyard BPR key CSFâ€™s forits BPR project. The finding was made using Force Field Analysis between Shipyard BPR teammembers and the established BPR key CSFâ€™s which will help to further understand how to implementBPR project effectively and successfully without incurring further delay in cost and time to theShipyard.Â